Role of rutin in 5-Fluorouracil-induced intestinal mucositis : prevention of histological damage and reduction of inflammation and oxidative stress - Fideles, Lázaro de Sousa (2020)
Intestinal mucositis, characterized by inflammatory and/or ulcerative processes in the gastrointestinal tract, occurs due to cellular and tissue damage following treatment with 5-fluorouracil (5-FU). Rutin (RUT), a natural flavonoid extracted from Dimorphandra gardneriana, exhibits antioxidant, anti-inflammatory, cytoprotective, and gastroprotective properties. However, the effect of RUT on inflammatory processes in the intestine, especially on mucositis promoted by antineoplastic agents, has not yet been reported. In this study, we investigated the role of RUT on 5-FU-induced experimental intestinal mucositis. Swiss mice were randomly divided into seven groups: Saline, 5-FU, RUT-50, RUT-100, RUT-200, Celecoxib (CLX), and CLX + RUT-200 groups. The mice were weighed daily. After treatment, the animals were euthanized and segments of the small intestine were collected to evaluate histopathological alterations (morphometric analysis); malondialdehyde (MDA), myeloperoxidase (MPO), and glutathione (GSH) concentrations; mast and goblet cell counts; and cyclooxygenase-2 (COX-2) activity, as well as to perform immunohistochemical analyses. RUT treatment (200 mg/kg) prevented 5-FU-induced histopathological changes and reduced oxidative stress by decreasing MDA concentrations and increasing GSH concentrations. RUT attenuated the inflammatory response by decreasing MPO activity, intestinal mastocytosis, and COX-2 expression. These results suggest that the COX-2 pathway is one of the underlying protective mechanisms of RUT against 5-FU-induced intestinal mucositis.